My Mother Dances in Me: a history of South Asian Dance by South African Indian women through the lens of a family archive as a lived experience - Pillay, Anusia (My University, 2019)
This research draws on my mother’s and my own life-long experience as Indian Classical dancers. Born to the initiator of Indian Classical dance in South Africa, I grew up, as a descendant of indenture, in the Apartheid system; I witnessed the devastating effects it had on our country, as a result of colonialism and imperialism. My family has been intrigued by the role of Dance as a healing art form. This has resulted in the accumulation of an archive spanning 2 generations and 59 years. During apartheid there appeared to be a trend in the field of dance, where anything deemed “different” was also seen as “unworthy”. South Asian Dance pedagogy has been a neglected area of scholarly work in South Africa, despite the Indian Diaspora’s presence in this country for 158 years. A strong historical record and archive of the advent foundation of Indian classical dance, especially the contributions by South Africans in reclaiming their cultural rights and identity from indenture, is a scarce resource in the South African dance community and academic landscape to date. Historical distortion/manipulation of facts and events, as well as the realisation that my family and I are cultural/dance activists, have brought me to a point in my life and career to be able to ask pertinent questions such as who/what constitutes “pioneering” in this field? And why is the South African dance community using western/colonial values to measure all other dance forms? As a tool of healing, Dance is viewed posthumously through the experiences and events documented by first my mother, both of us, and then myself on her passing. The archive is viewed through a historical (the traditions and developments from ancient Indian), activist and; feminist lens to recount the contributions of women of colour or the other to the South African dance and socio-political landscape. As an instrument of Peace and Nation building, dance has been and is employed to deal with life crises; for conflict resolution, to revitalise the traditional, and to transform the present and future - in my family’s case both professionally with students and practitioners and in a personal capacity. This work, an auto-ethnographic, case study, is a celebration of the pioneering work started by my mother and aunt (in 1959) in Indian dance, and the ensuing evolution into Multicultural and Intercultural dance. It traces the pioneer that I have become as a result - a journey from personal to cultural significance; a worthy contribution to the rich arts and culture tapestry that encompasses the South African identity and future South Asian dance pedagogy- a lived experience or process.
Thesis as a fulfillment of the Degree Master of Arts (Drama) by Thesis at the University of the Witwatersrand, 2019